In-Silico Exploration of Antiasthmatic Properties of Flavonoids Isolated from Lanneacoromandelica (Houtt.) Merr - Swathi S,; Lakshman K, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Lanneacoromandelica (Houtt.) Merr. (LC) is an important Indian medicinal plant used in folklore medicine to treat various diseases.Current study adopted chromatographic and analytical techniques for isolating phytochemicals and to recognise protein-ligand interactions, assessantiasthmatic potential against specific molecular targets.The L. coromandelicaleaf extract was subjected to column chromatography using silica gel with gradient mobile phases and two isolated compounds.The structures were established using detailed spectral analyses, such as mass spectrometry, FT-IR, 1H NMR, and 13C NMR.Molecular docking analysis was performed for these isolated molecules and their interactions with targets, such as 1IJZ Human IL (13), 3NOS (nitric oxide synthasised by human endothelial cells), 3LB6(IL-13 in complex with IL-13R alpha2), 1N26 (Human Interleukin-6 Receptor alpha), and 2AZ5 (TNF-alpha) which are important in the pathophysiology of asthma.Phytochemical examination detected the presence of diverse phytochemicals, and isolation through column chromatography led to the separation of Lupeol and Isoquercitrin in pure form.Molecular docking analysis revealed potential interactions between these ligands and the selected target molecules suggesting their involvement in the antiasthmatic properties of L. coromandelica.One flavonoid and One triterpenoid were isolated from the leaves of L. coromandelicaand in silico docking studies revealed good binding interactions with the targets involved in asthma, that guide further in-vitro and in-vivo studies.L. coromandelica